Relief Effects of Icariin on Inflammation-Induced Decrease of Tight Junctions in Intestinal Epithelial Cells - Li, Yanli; Liu, Jie; Pongkorpsakol, Pawin; Xiong, Zhengguo; Li, Li; Jiang, Xuemei; Zhao, Haixia; Yuan, Ding; Zhang, Changcheng; Guo, Yuhui; Dun, Yaoyan (Frontiers in Pharmacology, 2022)
Inflammatory cytokines including TNF-α and IL-1β impair intestinal barrier function in aging by disrupting intestinal tight junction integrity. Icariin (ICA) has a variety of pharmacological effects. Indeed, ICA produces anti-inflammatory, anti-oxidative stress, and inhibitory effects on microRNA (miRNA) expression. This study was to explore whether ICA could alleviate inflammation-associated intestinal barrier function impairment in aging and its underlying mechanism. Of particular interest, network pharmacology prediction indicated the potential therapeutic impacts of ICA for the treatment of colitis. Then, rats were used to study whether ICA has a protective effect on the reduction of tight junctions caused by inflammatory cytokines. Next, Caco-2 cell monolayers were used to explore the mechanism by which ICA alleviates the breakdown of tight junctions. Network pharmacology prediction revealed that ICA alleviated colitis via suppressing oxidative stress. After ICA intervention, expression of inflammatory cytokines was reduced, but tight junctions, antioxidant enzymes in aging rats were up-regulated. ICA reversed the TNF-α-induced a decrease in abundance of Occludin protein in Caco-2 cell monolayers. Meanwhile, ICA alleviated the increase in permeability and expression of miR-122a. However, the protective effect of ICA was markedly attenuated after transfection with miR-122a mimics. In conclusion, ICA reversed inflammation-induced tight junction disruption in vitro and in vivo, and the protective effect was exerted by reducing the expression of miR-122a and decreasing the release of inflammatory cytokines due to oxidative stress.